2022
DOI: 10.31763/ijrcs.v2i2.701
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Magnet Synchronous Generator Connected to a Grid via a High Speed Sliding Mode Control

Abstract: Wind power generation has recently received a lot of attention in terms of generating electricity, and it has emerged as one of the most important sources of alternative energy. Maximum power generation from a wind energy conversion system (WECS) necessitates accurate estimation of aerodynamic torque and system uncertainties. Regulating the wind energy conversion system (WECS) under varying wind speeds and improving the quality of electrical power delivered to the grid has become a difficult issue in recent ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The system comprises a generator coupled to a shaft that transforms the rotor's rotation into electrical energy. Due to its high efficiency, low maintenance cost, easy controllability, and high power density, the variable speed direct drive permanent magnet synchronous generator (PMSG) is now widely employed in wind power systems [17]. However, the generator model is analyzed using the dq reference frame and its voltage equation is given as ( 2) and (3).…”
Section: Wind Turbine Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The system comprises a generator coupled to a shaft that transforms the rotor's rotation into electrical energy. Due to its high efficiency, low maintenance cost, easy controllability, and high power density, the variable speed direct drive permanent magnet synchronous generator (PMSG) is now widely employed in wind power systems [17]. However, the generator model is analyzed using the dq reference frame and its voltage equation is given as ( 2) and (3).…”
Section: Wind Turbine Modelmentioning
confidence: 99%
“…The frequency of the system is affected by changes in load. The following expression represents the transfer function for the change as (17).…”
Section: Load Modelmentioning
confidence: 99%
“…The wind turbines in this study employ Permanent Magnet Synchronous Generator dynamic model, developed in direct and quadrature (d-q) rotating reference. Their voltage equations can be written as [11]:…”
Section: Permanent Magnet Synchronous Generator Pmsg Modelmentioning
confidence: 99%
“…Several were done on RERs' integration into national electric grids to enhance power quality issues [9][10][11][12][13]15,17]. Study in [9] gives a decarbonization pathway in the United States and how to satisfy American reduction targets of GHG emission.…”
Section: Introductionmentioning
confidence: 99%
“…The sliding mode control is a robust nonlinear controller which can easily handle a system's nonlinearity, uncertainty and model mismatch [49]- [52]. It has been implemented to control both linear and nonlinear systems: hydraulic [53][54], single machine infinite bus system [55], inverted pendulum [56]- [58], DC motor [59], induction motor [60], suspension [61], permanent magnet synchronous generator [62], hyperchaotic system [63], quadcopter [64], mobile robot [65][66], stepper motor [67], tank system [68] and robot manipulator [69]. According to study findings, SMC has been reported to give promising results.…”
Section: Introductionmentioning
confidence: 99%